posted by .

Simplify I came up with 5.5

(15x^5-21x^4+21x^2)/(3x^2 )

not sure if I did this the correct way it just doesn't seem right at all.

  • Math -

    divide each term by 3x^2

    5x^3 -7x^2+7

    check that.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Intermediate Algebra

    Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2 16x^2 - 2x + 5x^2 - 3x/2x^2 =21x^2 - 5/2x^2 Find the LCD 6/7z- 28, 8/x^2 -4x = 7x(x-4) Simplify 3x^2 - 2x/15x-10 = x/5 Let's start by looking at
  2. MATH

    This problem makes no sence to me i tried it but i know i am completely wrong someone please help. The cost for a long-distance telephone call is $0.36 for the first minute and $0.21 for each additional minute or portion thereof. Write …
  3. Algerbra

    how do you solve 7(3x+4)=8(2x+5)+13 expand the parenthesis...I will do the left side.. 21x + 29= Now, subtract sixteen x from both sides, and subtract 28 from both sides. I will be happy to check your work. 7(3x+4)=8(2x+5)+13 21x + …
  4. inequality expresion

    The cost of a long distant telephone call is $0.36 for first minutes and $0.21 each additional minutes or portion thereof. Write an inequality representing the number of minutes a person could talk with out exceeding $3.00 would this …
  5. algerbra

    7(3x+4)=8(2x+5)+13 how would I start a equation like this would it be 21x+28=16x+40+13 ?
  6. Algebra

    Is this right? 7(3x-2)=70 21x-14=70; 21x-14+14=70+14; 21x=84; x=4
  7. Algebra

    Is this right? 7(3x-2)=70 21x-14=70; 21x-14+14=70+14; 21x=84; x=4
  8. Algebra

    Factor. 15x^4 - 18x^3 + 21x^2 - 9x The method that I usually use did not seem to work... so I'm not sure if I messed up or not. Please help if you can and explain how you did it! Thank you! :-)
  9. math

    *simplify by combining like terms, if possible. then, remove the GCF and factor fully. 2x^2-21x+36+x^2 =3x^2-21x+36 ...i'm not sure what to do after that, could you help and show the steps please
  10. lomas

    Right answer? 15(x^2+3x) + 7(x^2+3x) - 5(x^2+3x) 15x^2+45x+7x^2+21x + 5(-x^2-3x) 15x^2+45x+7x^2+21x-5x^2-15x 17x^2+51x

More Similar Questions